Analisis Mitigasi Risiko Dalam Pembiayaan KPR Subsidi Pasca Pandemi Covid-19 Pada Bank BTN Syariah - Gumay, Jannah Marwiyah; Isfandayani, Isfandayani (At-Tamwil: Journal of Islamic Economics and Finance, 2024)
This research aims to find out what financing risks occur, how to implement financing risk mitigation, and to find out risk mitigation strategies for Subsidized BTN KPR Financing carried out by Bank BTN Syariah to minimize problematic financing after the Covid-19 pandemic. This research method uses a qualitative approach with descriptive methods. In this research, Bank BTN Syariah is one of the financial institutions in Cibubur. The sample collection technique used a purposive sampling technique, namely 4 employees at Bank BTN Syariah. Data collection techniques used observation, interviews and documentation with data analysis using the Miles and Huberman approach. The results of this research are the financing risks that occur in Subsidized BTN KPR Financing, namely the financing risks caused by customers failing to pay. Financing risk mitigation carried out by Bank BTN Syariah for Subsidized BTN KPR Financing is by identifying risks, measuring risks, monitoring risks and controlling risks. Meanwhile, the risk mitigation strategy carried out by Bank BTN Syariah for Subsidized BTN KPR Financing is by using the 5 C principles including Character, Capital, Condition of Economy, Capacity, and Collateral. Apart from that, the mitigation strategy carried out by Bank BTN Syariah after the Covid-19 pandemic was by implementing several approaches, namely a purchasing strategy approach based on community needs, a friendship approach with customers during the Covid-19 pandemic; and implementing the Covid-19 restructuring policy.